Strongyloides stercoralis contamination and risk factors in market vegetables: hidden dangers of communities living under poverty plate - Chalachew Yenew; Almaw Genet Yeshiwas; Gashaw Melkie Bayeh; Tilahun Degu Tsega; Sintayehu Simie Tsega; Asaye Alamneh Gebeyehu; Getaneh Atikilt Yemata; Rahel Mulatie Anteneh; Amare Genetu Ejigu; Ahmed Fentaw Ahmed; Zeamanuel Anteneh Yigzaw; Abathun Temesgen; et al. (Journal of Health, Population and Nutrition)
Abstract Background Strongyloidiasis, caused by Strongyloides stercoralis (S. stercoralis) spreads through environmental contamination and poor food safety, posing high risks in especially in tropical regions. However, limited research exists on the contamination and transmission pathways in local markets. This study evaluated S. stercoralis exposure, the likelihood of occurrence of risk, and associated risk factors in vegetables to enhance food safety. Methods A cross-sectional study that involved both field and laboratory investigations was conducted in Debre Tabor City, Ethiopia, analyzing S. stercoralis contamination in 360 randomly selected vegetable samples collected from five randomly selected markets. Standard parasitological techniques were used to detect larvae, and structured questionnaires were administered to vendors. One-way ANOVA, risk score and logistic regression were employed using SPSS version 28.0. Results The overall prevalence of S. stercoralis contamination in vegetables was 32.5%, with the highest contamination rates observed in leafy vegetables such as lettuce (26.9%) and cabbage (26.4%). The overall estimated risk score of Strongyloidiasis occurrence is 0.61, with the highest risk from leafy vegetables (lettuce: 1.00, cabbage: 0.89, spinach: 0.87) and the lowest from green pepper (0.14). Lettuce had 2.3 times higher odds of contamination compared to non-leafy vegetables. Vendors with no formal education had 3.6 times higher odds (AOR: 3.6, 95% CI: 2.02–6.54) of selling contaminated vegetables than those with secondary education or higher. Untrimmed fingernails were associated with a 4.8-fold increased risk (AOR: 4.8, 95% CI: 2.81–8.12) of contamination. Afternoon-collected vegetables had 2.02 times higher odds (AOR: 2.02, 95% CI: 1.17–3.51) of contamination than morning-collected samples. Transporting vegetables by carts significantly increased contamination risk (AOR: 3.7, 95% CI: 1.74–7.71) compared to car transportation. Conclusions and recommendations The findings identified leafy vegetables as a significant risk factor for exposure to S. stercoralis. Targeted interventions, improved hygiene, proper handling, and food safety policies are essential to mitigate S. stercoralis contamination risks.